FT-IR spectroscopic investigation of adsorption of pyrimidine on sepiolite and montmorillonite from Anatolia - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2003)
The adsorption of pyrimidine ( PM) on natural montmorillonite and sepiolite from Turkey was investigated by FT-IR spectroscopy. The intercalation of PM within montmorillonite has been shown by X-ray diffraction to increase the interlayer spacing. The spectroscopic results indicate that PM molecules adsorbed on sepiolite are coordinated to Lewis acidic centers or surface hydroxyls by H-bonding interaction through one of the pyrimidine ring nitrogen lone pairs. Moreover, some of the adsorbed PM molecules may enter the interior channels of the sepiolite structure and replace zeolitic water. The intercalated PM molecules within montmorillonite are coordinated to exchangeable cations directly or indirectly through water bridges.
Keywords: adsorption; clay minerals; diazines; intercalation; IR spectroscopy; montmorillonite; pyrimidine; sepiolite; Group Clay-Minerals; Pyridine; Cyclohexylamine; Desorption; Complexes